The assessment of Metro Manila Development Authority's Intelligent Transportation System (ITS) - Dayao, Athena (University of the Philippines Diliman, 2015)
The Philippines has long suffered from traffic congestion especially in Metropolitan Manila. Projects implemented by Metro Manila Development Authority (MMDA) and other traffic governing agencies such as Traffic Engineering Center (TEC). Tratfic Management Agency (TMA), Department of Transportation and Communication (DOTC) and Land Transportation Office (LTO) had had been omnipresent. Billions of pesos are wasted on lost productivity, missed business opportunity, wasted fuel and additional air pollutants, not to mention other unquantifiable aspect such as the quality of life.